Contribution of Teacher Personality Competence in Improving Student Motivation at MTs Al-Ma'arij - Ujang Natadireja; Kun Nurachadijat (P3M IAI Nusantara Batang Hari, 2024)
This study aims to explore and understand the relationship between teacher personality competencies and student motivation in high school environments. In this study, a qualitative approach was used with the case study method to explore a deep understanding of teacher and student experiences related to teacher personality competencies and student learning motivation. The research participants consisted of six teachers and twenty students who were purposively selected from Madrasah Tsanawiyah (MTs) Al-Ma'arij in the Sukabumi Regency area. Data collection was carried out through in-depth interviews with teachers and students, class observations, and analysis of related documents. Data were analyzed using thematic analysis and triangulation approaches to identify patterns, themes, and relationships emerging from the qualitative data. The results of the study show that the teacher's personality competence has a significant impact on students' learning motivation. Teachers who have a positive attitude, empathy, and are able to establish good relationships with students can increase their motivation to learn. In addition, effective communication and the teacher's ability to motivate students intrinsically are also important factors that influence student motivation. In this context, the teacher's personality competence has broad implications in increasing student learning motivation. Teachers need to develop a positive attitude, improve interpersonal skills, and integrate learning strategies that encourage student motivation. The results of this study can make a valuable contribution to the development of the teaching profession and the improvement of educational policies related to the development of teacher personality competencies.